Royalty Regulatory Framework Arrangements for Commercial Music Concert Performances (Case Ruling Number 825 K/Pdt.Sus-HKI/2025) - Muzacky Amri; Nabilla Desyalika Putri (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
This study aims to answer the research question of how copyright protection is enforced by songwriters in the context of commercial music use, specifically during music concerts, by analyzing Supreme Court Decision Number 825 K/Pdt.Sus-HKI/2025. The growth of Indonesia's music industry has increased the number of music concerts, often seen as a commercial way to exploit songs. However, royalty management at these concerts still faces legal challenges, especially in identifying who is responsible for paying royalties. This issue is exemplified by the copyright dispute between Agnez Mo and Ari Bias, which led to Supreme Court Decision Number 825 K/Pdt.Sus-HKI/2025. The research employs a normative juridical approach, incorporating legislative and case study methods. The study's findings show that the normative regulation governing music concert royalties in Indonesia designates event organizers as economic operators accountable for royalty payments via the National Collective Management Organization. Supreme Court Decision Number 825 K/Pdt.Sus-HKI/2025 affirms that vocalists cannot be automatically obligated to pay royalties unless it is demonstrated that they have received direct economic benefits. This ruling offers legal clarity and establishes a significant precedent in the enforcement of copyright law concerning music performances.